PENGEMBANGAN KARAKTER MULTIKULTURAL MAHASISWA DALAM PEMBELAJARAN CIVIC EDUCATION (Studi Pada Mahasiswa Jurusan KPI Fakultas Dakwah IAIN Salatiga) - Rasimin Rasimin (IAIN Salatiga, 2016)
Multicultural was resulted from the effect of intersection of individual right among society or civil right in state. Multicultural as the base essence is able to resist the violence existence. This research used Research and Development (RD) method. This research showed that: (a) the modernization progress in Salatiga influenced the shifting of social life in the students social environment. (b) Communication and Broadcasting of Islam Department (KPI) of Dakwah Faculty positively appreciated model of multicultural character development in civic education learning because it was regarded as innovative model and appropriate with the environment of social society of students. (c) Model of multicultural character development was effective to develop the awareness of tolerant among students. (d) Lecturers were able to deliver civic education material using this model. (e) The supremacy of this model was in the learning objective, affective aspect became the main target, while cognitive and psychomotor aspect became proponent factor. Abstrak Multikultural merupakan bentuk sikap persinggungan hak individu dalam masyarakat. Multikultural sebagai ukuran esensial yang mampu meminimalisisr terjadinya kekerasan. Penelitian menggunakan pendekatan Research and Development (RD). Hasil penelitian menujukan bahwa: (a) Kemajuan kota Salatiga terhadap modernisasi yang mempengaruhi pada bergesernya kehidupan bermasyarakat di lingkungan sosial mahasiswa. (b) Jurusan KPI Fakultas Dakwah menyambut positif model pengembangan karakter multikultural dalam pembelajaran civic education karena dianggap inovatif. (c) Model pengembangan karakter multikultural efektif meningkatkan kesadaran bertoleransi mahasiswa. (d) Dosen memiliki kompetensi untuk dapat menyampaikan materi kuliah civic education menggunakan model pengembangan karakter multikultural. (e) Keunggulan model ini terletak pada tujuan pembelajaran, aspek afektif menjadi target utama sementara aspek kognitif dan aspek psikomotor menjadi faktor pendukung.